Deciphering the global roles of Cold shock proteins in Listeria monocytogenes nutrient metabolism and stress tolerance - Muchaamba, Francis; von Ah, Ueli; Stephan, Roger; Stevens, Marc J. A.; Tasara, Taurai (Frontiers in Microbiology, 2022)
Listeria monocytogenes (Lm) accounts for serious public health and food safety problems owing to its stress resilience and pathogenicity. Based on their regulatory involvement in global gene expression events, cold-shock domain family proteins (Csps) are crucial in expression of various stress fitness and virulence phenotypes in bacteria. Lm possesses three Csps (CspA, CspB, and CspD) whose regulatory roles in the context of the genetic diversity of this bacterium are not yet fully understood. We examined the impacts of Csps deficiency on Lm nutrient metabolism and stress tolerance using a set of csp deletion mutants generated in different genetic backgrounds. Phenotype microarrays (PM) analysis showed that the absence of Csps in ∆cspABD reduces carbon (C-) source utilization capacity and increases Lm sensitivity to osmotic, pH, various chemical, and antimicrobial stress conditions. Single and double csp deletion mutants in different Lm genetic backgrounds were used to further dissect the roles of individual Csps in these phenotypes. Selected PM-based observations were further corroborated through targeted phenotypic assays, confirming that Csps are crucial in Lm for optimal utilization of various C-sources including rhamnose and glucose as well as tolerance against NaCl, β-phenyethylamine (PEA), and food relevant detergent stress conditions. Strain and genetic lineage background-based differences, division of labour, epistasis, and functional redundancies among the Csps were uncovered with respect to their roles in various processes including C-source utilization, cold, and PEA stress resistance. Finally, targeted transcriptome analysis was performed, revealing the activation of csp gene expression under defined stress conditions and the impact of Csps on expression regulation of selected rhamnose utilization genes. Overall, our study shows that Csps play important roles in nutrient utilization and stress responses in Lm strains, contributing to traits that are central to the public health and food safety impacts of this pathogen.